Assessment in Music Education: from Policy to Practice
XV, 296 p. 36 illus., 16 illus. in color.
Keywords: The contributions to this volume aim to stimulate discussion about the role of assessment in the learning experiences of students in music and other creative and performing arts settings. The articles offer insights on how assessment can be employed in the learning setting to enhance outcomes for students both during their studies at higher education institutions and after graduation. An international group of leading researchers offers an exciting array of papers that focus on the practice of assessment in music, particularly in higher education settings. Contributions reflect on self-, peer- and alternative assessment practices in this environment. There is a particular emphasis on the alignment between assessment, curriculum structure and pedagogy.